1977
DOI: 10.1590/s0037-86821977000100002
|View full text |Cite
|
Sign up to set email alerts
|

Estudos sobre a epidemiologia da doença de Chagas no estado do Ceará - Brasil VI - estudos em uma micro-área de russas

Abstract: taxa de p o s itiv id a d e g lo b a l para 29,5% . Nessa m icro-área fo ra m exam inados 125 pessoas pela R FC e p e lo xe n o d ia g n ó stico , encontrando-se um a p o s itiv id a d e de 7,2%. Desses p o s itiv o s , 55% residem em casas com a n im a l p o s itiv o , sendo que duas casas apresentaram duas pessoas p o s itiv a s cada. Do to ta l de xenos som ente d ois fo ra m p o s iti vos. Na m icro-área fo ra m ca ptu ra d os 4 0 5 tria to m fn e o s , com 27,7% p o s itiv o s , d e n tro e fo ra das casa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In Miguel Pereira, as in most rural communities, residents extract timber from the natural environment for construction of houses, animal shelters and fences. This wood is often stored for long periods of time in peridomicile areas, inevitably serving as shelters for synanthropic animals 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In Miguel Pereira, as in most rural communities, residents extract timber from the natural environment for construction of houses, animal shelters and fences. This wood is often stored for long periods of time in peridomicile areas, inevitably serving as shelters for synanthropic animals 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirms the existence of an endemic area for CD in the municipality of Quixeré, Ceará. This fact is known from the time the first studies were performed by Alencar in 1963, showing an estimated seroprevalence of 22.5% 9 . We showed that the seroprevalence rate of CD in Quixeré was 3.7% higher than that reported in other studies performed in the state of Ceará (3.1% 10 , 1.2% 11 , and 1.2% 12 ) and lower than that reported in a study performed by Freitas et al (2017) in the municipality of Limoeiro do Norte (4.2%, 34/812) 11 .…”
mentioning
confidence: 81%
“…Nessa região, o Triatoma brasiliensis e o Triatoma pseudomaculata são consideradas as principais espécies vetoras pelo fato de serem as espécies prevalentes no ambiente domiciliar (Forattini, 1980). O espaço ecológico ocupado por essas duas espécies não se restringe ao ambiente domiciliar (Alencar et al, 1977a), podendo também ser estendido aos ambientes modificados que circundam as moradias humanas (Alencar & Bezerra, 1977) e ao ambiente silvestre (Alencar et al, 1977b). Acredita-se que essa valência ecológica seja o principal obstáculo ao controle efetivo destas duas espécies vetoras através da aplicação intradomiciliar de inseticidas.…”
Section: Introductionunclassified